Predicting creep settlements of foundations in permafrost from the results of cone penetration tests - Ladanyi, Branko; Lunne, Tom; Vergobbi, Pierre; Lhuillier, Bernard (Canadian Geotechnical Journal, 1995)
As a joint research project sponsored by the French–Norwegian Foundation for Scientific and Industrial Research, the Norwegian Geotechnical Institute, Geodia/Geocean, and École Polytechnique have carried out in the summer of 1990 a series of special in situ pressuremeter and cone penetration tests at a permafrost site in Longyearbyen, Svalbard. The purpose of the testing program was to compare the results of the two different field testing methods and to check the potential of such methods for serving as a basis for prediction of the behaviour of foundations in permafrost. As pressuremeter test results have been presented in a previous publication, this paper shows only the results of cone penetration tests and their interpretation in terms of strength and creep parameters of the frozen soil. Subsequently, the same data are used to predict the behaviour under long-term axial load of two prefabricated and one cast-in-place concrete pile that were tested by the Selmer Furuholmen Anlegg A.S. in cooperation with the Norwegian Geotechnical Institute at the same site for 3 years. Key words : permafrost, cone penetration tests, piles field loading tests, creep settlement.